2013
DOI: 10.1371/journal.pone.0056069
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Activation of Neurotensin/IL-8 Pathway in Hepatocellular Carcinoma Is Associated with Increased Inflammatory Response in Microenvironment, More Epithelial Mesenchymal Transition in Cancer and Worse Prognosis in Patients

Abstract: AimTo investigate the role of neurotensin (NTS) in hepatocellular carcinoma (HCC) sub- grouping and the clinical and pathological significance of activation of NTS/IL-8 pathway in HCC.MethodsThe genome-wide gene expression profiling were conducted in 10 pairs of cancer tissues and corresponding normal adjacent tissues samples using Affymetrix GeneChip® Human Genome U133 Plus 2.0 microarray to screen differentially expressing genes and enrich dysfunctional activated pathways among different HCC subgroups. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…The fact that neutrophils are frequent residents of solid tumors is not surprising as many of these tumors express and secrete high levels of neutrophil mobilizing factors and neutrophil chemoattractants. For example, IL-8/CXCL8, a potent neutrophil chemotactic factor and activator, was found to be expressed in a wide variety of human cancers [253,[269][270][271][272]. In most cases, IL-8 is secreted by the tumor cells themselves [210], while in others, other stromal cells such as fibroblasts [273] and macrophages [274] secrete IL-8.…”
Section: Neutrophils At the Primary Tumor Sitementioning
confidence: 99%
“…The fact that neutrophils are frequent residents of solid tumors is not surprising as many of these tumors express and secrete high levels of neutrophil mobilizing factors and neutrophil chemoattractants. For example, IL-8/CXCL8, a potent neutrophil chemotactic factor and activator, was found to be expressed in a wide variety of human cancers [253,[269][270][271][272]. In most cases, IL-8 is secreted by the tumor cells themselves [210], while in others, other stromal cells such as fibroblasts [273] and macrophages [274] secrete IL-8.…”
Section: Neutrophils At the Primary Tumor Sitementioning
confidence: 99%
“…It has recently been suggested that IL-8 could promote cancer cell metastasis via autocrine and paracrine means which is associated with enhanced epithelial-mesenchymal transition (EMT). [21][22][23] However, the effect of IL-8 on the MT of glioma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that IL-8 plays a critical role during tumor angiogenesis, growth and metastasis in colon, gastric and pancreatic carcinoma [10][11][12]. Moreover, IL-8 has been found to have prognostic value in a variety of malignancies, including hepatocellular and nasopharyngeal carcinoma, gastric, lung and prostate cancer [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%